Multidisciplinary research: should effort be the measure of success?. Issue 5 (4th July 2017) - Buswell, Richard; Webb, Lynda; Mitchell, Val; Leder Mackley, Kerstin
ABSTRACT: Energy demand reduction and flexible demand from dwellings will play a critical role in achieving a low-carbon future. There remain many unanswered questions around the interaction of people with their environment and the technical systems that service them and, as a result, multidisciplinary research is a principal component of research funding internationally. However, relatively little published work considers the operational issues in undertaking epistemologically diverse, academic research projects. This paper makes a contribution by quantifying the operational effort involved in data collection on a large multidisciplinary project and connecting the operational issues encountered to knowledge production. It is found that the cost of the data gathering is £46, 000/home, and participants can give upwards of 217 hours of their time per house engaging with data-gathering activities. The rate of knowledge production is found to be approximately three publication/full-time equivalents (FTE) over the lifetime of the project and the risk to generating interdisciplinary insights is shown to be dependent on largely unforeseeable operational issues that compound the characteristic differences in the collection of the data utilized by social and technical research communities.